Investigation of energy efficiency of hydrogen production in alkaline electrolysers - Lysenko, Olha; Ikonnikov, Valerii (Technology audit and production reserves, 2023)
The object of research is the energy efficiency of the electrolysis process in electrolyzers with alkaline electrolyte electrical parameters. The existing problem consists in obtaining the energy efficiency of the process in an electrolyzer with an alkaline electrolyte of more than 65 %. To solve this problem, it is proposed to manufacture an electrolyzer with metal electrodes made of stainless steel and separated from each other by a gas-tight membrane (Bologna cloth) to separate hydrogen and oxygen gases. To establish the energy efficiency characteristics, an experimental installation was made, and the necessary measuring equipment was also used. In the course of the work, a research methodology was developed and the necessary calculation of the measured values was carried out. As a result, the influence of the operating voltage on the consumption of the current flowing through the electrodes of the electrolyzer and the power consumed by it was revealed, the values of which increase with the increase of the operating voltage. It was established that the energy efficiency of the process in electrolyzers with an alkaline electrolyte decreases with an increase in the operating voltage. At operating voltages of 3 V, 4 V, and 5 V, the energy efficiency is 85.7 %, 77 %, and 70 %, respectively. The proposed technique involves conducting experimental studies directly on a functioning electrolyzer. The practical implementation of the use of a gas-tight membrane (Bologna fabric) can help reduce the cost of manufacturing an electrolyzer. Therefore, the presented research will be useful for the industrial production of hydrogen.